Kode Etik dan Etika Profesi - Jeffry Yuliyanto Waisapi (PT FORMOSA CENDEKIA GLOBAL, 2022)
The professional code of ethics is the criteria for professional principles that have been outlined, so that it is known with certainty the professional obligations of old, new, or prospective members of a professional group. The professional code of ethics has determined the standardization of professional obligations of members of professional groups. So that the government or the public does not need to intervene to determine how professionals carry out their obligations. The professional code of ethics is basically a behavioral norm that is considered correct or already established and of course it is more effective if the behavioral norm is formulated properly, so as to satisfy all parties. The purpose of the code of ethics is for professionals to provide the best possible service to service users. The existence of a code of ethics will protect unprofessional actions. In professional ethics, a profession has a high moral commitment which is usually stated in the form of special rules that become a guide for everyone who develops the profession concerned. and adhered to by every profession. The goal is for professionals to provide the best services or products to the community and protect them from unprofessional actions, thereby gaining trust in the eyes of the public. The existence of a code of ethics that regulates the actions of a civil engineer or engineering graduate to avoid himself from all forms of action that will harm himself, society and the environment. So that the work should begin with sincere intentions and high moral commitment in order to develop the profession concerned. A Civil Engineer is required to work hard, be disciplined, not random and complete which must be balanced with smart work, namely following technological developments in their field, being innovative and able to solve problems in the best way.